Legal Review Of Contract Design Obligations Based On The Principle Of Good Faith And Negotiation Responsibility - SULAIMAN, SULAIMAN; Akbar Taufik Amrullah; Juliana (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The principle of good faith is a fundamental doctrine in Indonesian contract law, applying not only during the performance of a contract but also at the pre-contractual stage, particularly in negotiation and contract drafting. This study analyzes the regulation, application, and legal obligations arising from the principle of good faith before a contract is concluded, including the duties of disclosure, confidentiality, and serious negotiation. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that violations of good faith during negotiations may result in legal liability through tort based on the doctrine of culpa in contrahendo. Thus, the principle of good faith functions as a corrective mechanism to contractual freedom and as a protective instrument for weaker parties within contractual relations.